2013
DOI: 10.1002/dmrr.2406
|View full text |Cite
|
Sign up to set email alerts
|

Positive association between high‐sensitivity C‐reactive protein and incidence of type 2 diabetes mellitus in Japanese workers: 6‐year follow‐up

Abstract: These findings imply that higher hs-CRP itself or existence of chronic systemic inflammation precedes onset of T2DM independent of obesity and smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 53 publications
0
20
1
Order By: Relevance
“…11 A recent study of more than 4,000 subjects followed for six years revealed that elevated hs-CRP was associated with type 2 diabetes. 12 Another study with a follow-up of 11 years also demonstrated the same association of hs-CRP with diabetes. 13 As expected, patients with lower glycosylated hemoglobin (A1C) levels were found to have signifi cantly lower hs-CRP levels.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 72%
“…11 A recent study of more than 4,000 subjects followed for six years revealed that elevated hs-CRP was associated with type 2 diabetes. 12 Another study with a follow-up of 11 years also demonstrated the same association of hs-CRP with diabetes. 13 As expected, patients with lower glycosylated hemoglobin (A1C) levels were found to have signifi cantly lower hs-CRP levels.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 72%
“…Increasing evidence shows that T2DM is a low-grade inflammatory disease1. In patients with T2DM, serum levels of pro-inflammatory cytokines such as interleukin-1 beta (IL-1β), interleukin-6 (IL-6), and CRP (C-reactive protein) are elevated and have been widely used as a biomarker of T2DM1234. This is particularly important in those with DN56, suggesting a close relationship between inflammation and T2DM/T2DN.…”
mentioning
confidence: 99%
“…The mechanisms for independent and synergistic effects of passive smoking and obesity are not known. Cigarette smoke and environmental pollutants induce inflammatory responses, as does obesity‐induced insulin resistance . However, the specific inflammatory markers associated with smoking and insulin resistance may differ, as well as the tissues affected by inflammation.…”
mentioning
confidence: 99%